Oral health status of salivary vitamin D and estradiol in osteoporotic postmenopausal Iraqi women - Ameera Y Alamiry; Areej A Najm; Nurulhuda Mohd (Journal of Baghdad College of Dentistry)
Background: This study aimed to investigate the association between oral health with salivary vitamin D and estradiol in postmenopausal women in Iraq. Materials and Methods: in this cross-sectional comparative study, 90 participants were divided into three groups based on dual-energy X-ray absorptiometry data either (i) osteoporosis (ii) osteopenia; or (iii) healthy control. The questionnaire was used to measure level of xerostomia. Clinical parameters, including clinical attachment loss and missing teeth were recorded. Salivary flow rate was measured; and the salivary vitamin D and estradiol levels were evaluated using the enzyme-linked immunosorbent assay. Result: In the osteoporosis group, the average clinical attachment loss was significantly greater and statistically significant, while the missing teeth was considerably higher in the osteopenia group. Meanwhile, the control group showed the highest levels of salivary flow rate, vitamin D, and estradiol. A negative association was found between estradiol and tooth loss in the osteoporosis group. On the contrary, a moderately positive correlation was found between vitamin D and salivary flow rate in the control group. Conclusion: Osteoporosis negatively impacted oral health by increasing the number of missing teeth and clinical attachment loss and decreasing the flow rate of saliva. Salivary vitamin D and estradiol correlate with tooth loss and salivary flow rate, among other oral health conditions. Thus, a person’s level of dental health can be an early warning sign of osteoporosis.